PENGARUH LITERASI EKONOMI DAN SELF-CONTROL TERHADAP PERILAKU KONSUMTIF (Survey pada Guru Mata Pelajaran Ekonomi di Kota Bandung) - Yustika Nurul Amelia, - (2021)
the city of Bandung who tend to be irrational or consumptive behavior. This study aims to determine the description of economic literacy, self-control and consumptive behavior in economics subject teachers, and the effect of economic literacy and self-control on consumptive behavior. The method in this study uses an explanatory survey using questionnaires and online tests via google form as a data collection tool. The population in this study were 124 teachers of economics subjects in SMA Negeri and Private SMA in Bandung. By using random sampling technique, a sample of 62 teachers was obtained. The data analysis technique in this research is multiple regression analysis. The results showed that: (i) economic literacy in the high category; self-control in the high category and the level of teacher consumptive behavior is in the moderate category (ii) there is an effect of economic literacy and self-control on consumptive behavior simultaneously by 25.6% (iii) economic literacy and self-control have a negative effect on teacher consumptive behavior partially and simultaneously.